Knowledge and practices of dairy farmers relating to brucellosis in urban, peri-urban and rural areas of Assam and Bihar, India - Deka, Ram Pratim; Magnusson, Ulf; Grace, Delia; Shome, R.; Lindahl, Johanna F. (Informa UK Limited, 2020)
Background: Brucellosis is one of the most common zoonotic diseases in the world. This study aimed at assessing farmers’ knowledge about brucellosis as well as practices relevant to transmission of brucellosis and their associated determinants. Results: Few farmers knew about brucellosis (3.4%, n = 18) and its zoonotic importance (0.8%, n = 4). Knowledge about brucellosis was higher for farmers with a larger herd size (p < 0.001) and fully using a stall-fed system (p < 0.001). Training on dairy cattle management (p < 0.001), training on animal disease (p < 0.01), consultation with veterinarians (p < 0.001) and farms being in urban areas (p < 0.01) were also significantly positively associated with knowledge about brucellosis. No significant association was observed between farmers’ knowledge about brucellosis and state, family size, education, age or gender of the farmers. Farmers knowledge about brucellosis was significantly associated with certain practices that include use of disinfectant while cleaning farms (p < 0.05), animal movement (p < 0.01), introduction of new animals (p < 0.05) and raw milk consumption (p < 0.05). The study did not find any association between knowledge about brucellosis and method of disposal of aborted materials, personal hygiene and quarantine practices. Conclusion: More interaction with veterinarians and training on animal management may be an important tool for generating awareness among the farming community for reducing transmission of the disease.